Local-authority partnerships within the Urban regions of western Germany: Aspiration and political reality - Saller, Raymond (Raumforschung und Raumordnung | Spatial Research and Planning, 2000)
In conurbations, perhaps more than anywhere else, regional co-operation plays a key role in the delivery of local-authority services and tasks. Although, since the 1970s, all of Germany’s urban regions have instituted partnerships to bring together urban authorities and the rural authorities of the surrounding region, in the majority of cases these have been charged solely with co-ordinating the local-authority planning function, and only to a lesser degree with the joint delivery of local-authority services. With the completion of the European single market, many agglomerations have created stand-alone regional companies to work within the economic-development field. Attempts to intensify co-operation in other areas have however failed. Remedies to this problem are seen in varying the boundaries of urban regions and in the active support for voluntary partnerships provided by state governments.
Keywords: Article